Non-corrosive Green Lubricant With Dissolved Lignin in Ionic Liquids Behave as Ideal Lubricants for Steel-DLC Applications - Hua, Jing; Shi, Yijun (Frontiers in Chemistry, 2019)
Diamond-like carbon (DLC)–steel contacts become more and more popular in the industry now. Since the surface chemical properties of DLC are quite different from those of iron, traditional formulated lubricants have problems to form tribo-chemical films, which are effective to improve the tribological performance for steel-steel contacts, on the surface of DLC. Thus new lubricants formulation strategies are needed to be considered for steel-DLC applications. A kind of green lubricant (lignin-[Choline][L-Proline] (L-[CH][Pro])) without any traditional tribo-chemical active element, i.e., free of P, S, B, etc., was studied in this paper for the steel-DLC contact. To find the difference between this new ILs and the traditional lubricants, a commercially available fully formulated lubricant was used as a reference. An Optimol SRV-III oscillating friction and wear tester was used to evaluate the tribological performance. Three different kinds of commercially available DLC coatings (Tribobond 40(Cr + a-C:H:W), Tribobond 43((Cr+) a-C:H), and Tribobond 44(a-C:Cr)) were investigated. The results show that the ILs exhibit an obviously lower friction coefficient than that of the traditional commercially available fully formulated lubricant. Among those three DLC coatings, the (Cr+) a-C:H DLC coating exhibits the biggest improvement of wear resistance lubricated with the new ILs than that of the commercially available fully formulated lubricant. It’s expected that its excellent tribological properties are attributed to the affinity of the ILs to the metal surface and the strength of the ionic liquids interactions by hydrogen bonding. Thus, forming strong physical adsorption strategy, instead of forming chemical tribo-films, is recommended to enhance the lubricating performance of lubricants for DLC.